Collective spreading of red blood cells flowing in a microchannel. (1st March 2018) - Chuang, Cheng-Hsi; Kikuchi, Kenji; Ueno, Hironori; Numayama-Tsuruta, Keiko; Yamaguchi, Takami; Ishikawa, Takuji
Abstract: Due to recent advances in micro total analysis system technologies, microfluidics provides increased opportunities to manipulate, stimulate, and diagnose blood cells. Controlling the concentration of cells at a given position across the width of a channel is an important aspect in the design of microfluidic devices. Despite its biomedical importance, the collective spreading of red blood cells (RBCs) in a microchannel has not yet been fully clarified. In this study, we experimentally investigated the collective spreading of RBCs in a straight microchannel, and found that RBCs initially distributed in one side of the microchannel spread to the spanwise direction during downstream flow. Spreading increased considerably as the hematocrit increased, though the flow rate had a small effect. We proposed a scaling argument to show that this spreading phenomenon was diffusive and mainly induced by cell–cell interactions. The dispersion coefficient was approximately proportional to the flow rate and the hematocrit. These results are useful in understanding collective behaviors of RBCs in a microchannel and in microcirculation.